Pengaruh pemberian sari kacang hijau terhadap perubahan kadar hemoglobin pada remaja putri dengan anemia - Rofiah, Khofidhotur; Nirwana, Betanuari Sabda; Nikmah, Anis Nikmatul; Lutfiasari, Dessy; Wulandari, Siswi (Holistik Jurnal Kesehatan, 2025)
Background: Hemoglobin is made up of iron which is an O2 carrier. High and abnormal hemoglobin levels occur due to hemoconcentration due to dehydration. The number of red blood cells and hemoglobin molecules does not always increase and decrease simultaneously, for example, a decrease in red blood cells accompanied by a slight increase in hemoglobin levels or normal occurs in cases of pernicious anemia, as well as a slightly increased or normal level of red blood cell hemoglobin accompanied by decreased hemoglobin levels, occurs in iron deficiency anemia. Purpose: To determine the effect of mung bean juice on changes in hemoglobin levels in adolescent girls with anemia. Method: A quasi-experimental design with a pretest-posttest control group design was used. The study focused on adolescent girls at the Faculty of Health Sciences, University of Kediri. A sample of 40 participants was selected using purposive sampling and divided into two groups. Data were examined using paired t-tests. Results: Hemoglobin levels in the intervention group increased from 11.05±0.79 to 12.03±0.98 gr/dl after being given mung bean juice. The control group had an average hemoglobin concentration of 11.25±0.42 gr/dl before the test and decreased slightly to 11.20±0.62 gr/dl after the test, the intervention group showed a significant effect on hemoglobin levels before and after receiving mung bean juice (p=0.025), indicating a significant change in hemoglobin levels after the intervention. Conclusion: the administration of mung bean juice has a positive impact on increasing hemoglobin levels in anemic adolescent girls. Consider measuring ferritin levels and controlling participants' diets for more accurate results. College students are encouraged to regularly consume mung bean juice as an easy and affordable natural alternative to help increase hemoglobin levels and prevent anemia.   Keywords: Anemia; Green Bean Juice; Young Women.   Pendahuluan: Hemoglobin terdiri dari zat besi yang merupakan pembawa O2. Kadar hemoglobin yang tinggi dan abnormal terjadi karena hemokonsentrasi akibat dehidrasi. Jumlah sel darah merah dan molekul hemoglobin tidak selamanya meningkat dan menurun secara bersamaan, misalnya penurunan sel darah merah di sertai kadar hemoglobin yang sedikit meningkat atau normal terjadi pada kasus anemia pernisiosa, serta kadar hemoglobin sel darah merah yang sedikit meningkat atau normal disertai kadar hemoglobin yang menurun, terjadi pada anemia defisiensi zat besi. Tujuan: Untuk mengetahui pengaruh sari kacang hijau terhadap perubahan kadar hemoglobin pada remaja putri dengan anemia. Metode: Desain quasi eksperimen dengan pretest-posttest control group design. Penelitian difokuskan pada populasi remaja putri di Fakultas Ilmu Kesehatan Universitas Kediri. Sampel penelitian berjumlah 40 partisiapn yang dipilih dengan menggunakan teknik purposive sampling dan dibagi menjadi dua kelompok. Data diperiksa dengan uji beda berpasangan. Hasil: Kadar hemoglobin pada kelompok intervensi mengalami peningkatan dari 11.05±0.79 menjadi 12.03±0.98 gr/dl setelah diberikan jus kacang hijau. Kelompok kontrol memiliki rata-rata konsentrasi hemoglobin 11.25±0.42  gr/dl sebelum pengujian dan sedikit menurun menjadi 11.20±0.62 gr/dl setelah pengujian. Kelompok intervensi menunjukkan pengaruh yang signifikan terhadap kadar hemoglobin sebelum dan sesudah menerima jus kacang hijau (p=0.025), mengindikasikan perubahan yang berarti pada tingkat hemoglobin setelah intervensi. Simpulan: Pemberian sari kacang hijau memberikan dampak positif terhadap peningkatan kadar hemoglobin pada remaja putri anemia.   Kata Kunci: Anemia; Remaja Putri; Sari Kacang Hijau.